EFEKTIVITAS PENDIDIKAN DAN PELATIHAN PEGAWAI NEGERI SIPIL DALAM MENINGKATKAN KINERJA APARATUR (Suatu Studu di Badan Kepegawaian Daerah Kota Ternate) - SAMAD, FACHRY; Pangkey, Masje Silija; Rompas, Sonny (Sam Ratulangi University, 2015)
ABSTRAK This study aims to determine the effectiveness of the education and training of civilservants in improving the performance of the apparatus in Ternate City BKD; in other words, todetermine whether the education and training of civil servants effective in improving the performanceof the apparatus in BKD Ternate.This study used qualitative methods. Informants were taken from structural officials andemployees of the staff / implementers in BKD Ternate, entirely as many as 10 informants. Collectingdata using interview techniques, while the analysis of data using qualitative analysis techniquesinteractive model of Miles and Hubernann.The results showed: (1) Training civil servants (Structural / Leadership, Technical,Functional) can develop or improve the competence of knowledge, skills, and attitudes; (2) Training ofcivil servants may also develop personality, ethics and morals, and the dynamics of the mindset of theapparatus; (3) Training of civil servants provide benefits and positive impact on the ability to carry outthe task that in completing the task quickly and on time, manage and use the organization's resourcesefficiently, responding to the development of work tasks, make decisions, and handle and solveproblems in execution of duties ,Based on the results of these studies conclude that education and training of civil servantseffectively improve the performance of personnel in the Regional Employment Board of Ternate. Thismeans that more and higher education and training of civil servants who followed the higher orincreasing the performance of the apparatus.Based on the results of this study, it is necessary to put forward some suggestions (1) TrainingApparatus Training both Structural and Technical Training and Functional Training needs to beimproved. For the allocation of the budget (APBD) for Training Apparatus which has been felt stillvery small / minimal, needs to be improved. (2) Training of civil servants should be based on theprinciple of correspondence between the types of training with the objective needs and the realimplementation of the tasks at all levels in accordance with the principles of organizationaldevelopment. For that training should be based on sound analysis both at the organizational level, thelevel of the job / position and individual level.Keywords: Trainingcivil servants, Apparatus Performance